Nitrogen-containing resin liquid phase coated modified artificial graphite as well as preparation method and application thereof
By forming an N-doped carbon coating on the surface of artificial graphite, the problems of slow lithium ion transmission speed and limited lithium embedded position during the charging and discharging process of lithium-ion battery negative electrode materials are solved, and high magnification, high capacity and high first-term efficiency are achieved Modified artificial graphite.
Patent Information
- Application Number
- CN202411504332.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The lithium ion transmission speed of the negative electrode materials of existing lithium-ion batteries is slow during charging and discharging, the lithium embedded position is limited, and the SEI film is unstable, resulting in insufficient rate performance, capacity and first-term effect.
The modified artificial graphite is coated with nitrogen-containing resin to obtain nitrogen-containing phenolic resin through polycondensation reaction, and the N-doped carbonization layer is formed through liquid phase coating and high-temperature carbonization treatment, which improves the conductivity of the material and the lithium storage space. .
It significantly accelerates the transmission speed of lithium ions during charging and discharging, provides more lithium embedded position and stability SEI films, and improves the rate performance, capacity and first-time effect of modified artificial graphite.
Smart Images

Figure CN119480958A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to nitrogen-containing resin liquid-phase coated modified artificial graphite and a preparation method and application thereof. Background Art
[0002] Graphite is currently the most widely used negative electrode material for lithium-ion batteries in commercial applications. It has a good layered structure, which is conducive to the embedding and extraction of lithium ions during the charging and discharging process. Its theoretical capacity can reach 372mAh / g. As the requirements for miniaturization and lightweight of digital electronics, power vehicles and other products continue to increase, the requirements for the capacity, cycle life and rate performance of lithium-ion batteries are also increasing. In order to shorten the charging time of lithium-ion batteries, artificial graphite can be modified by coating, thereby improving the rate performance of lithium-ion batteries.
[0003] At present, the commonly used coating materials in industry include asphalt and resin. The coating methods include solid phase coating and liquid phase coating. The solid phase coating process is simple, but the consistency and uniformity are poor, which affects the coating effect, while the liquid phase coating has the advantages of low cost, uniform coating and good consistency. In addition, doping is also a common modification method for graphite. Non-metallic elements such as N, P, B, Si, or metal elements such as Fe, Co, Ni are added to the graphite structure. These elements can replace carbon atoms in graphite, or be inserted into the gaps between graphite layers to change the electronic structure of graphite. Graphite doped with elements can improve the stability of the SEI film, which is beneficial to improve the capacity and initial efficiency of the negative electrode material. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a nitrogen-containing resin liquid-phase coated modified artificial graphite and its preparation method and application. By using a nitrogen-containing phenolic resin to liquid-phase coat the artificial graphite and carbonize it at high temperature, a uniform and consistent N-doped carbon coating layer is formed on the surface of the artificial graphite, thereby effectively accelerating the transmission speed of lithium ions during the charging and discharging process, and at the same time having more lithium insertion sites and a stable SEI film, ultimately obtaining a modified artificial graphite with high rate, high capacity and high initial efficiency.
[0005] The present invention provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, comprising the following steps:
[0006] S1, subjecting N-phenylmaleimide, a phenolic compound, an aldehyde compound and a catalyst to a polycondensation reaction to obtain a nitrogen-containing phenolic resin;
[0007] S2, adding the nitrogen-containing phenolic resin and artificial graphite into a solvent for liquid-phase coating, and then performing carbonization treatment to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite.
[0008] In the present invention, N-phenylmaleimide, a phenolic compound, an aldehyde compound and a catalyst are subjected to a polycondensation reaction to obtain a nitrogen-containing phenolic resin, and then the nitrogen-containing phenolic resin and artificial graphite are subjected to liquid phase coating, so that a nitrogen-containing phenolic resin layer is coated on the surface of the artificial graphite, and then after high-temperature treatment, the nitrogen-containing phenolic resin layer can be carbonized to form an N-doped carbon shell layer, and coated on the surface of the artificial graphite, and finally the nitrogen-containing resin liquid phase coated modified artificial graphite is obtained;
[0009] Among them, N-phenylmaleimide directly participates in the phenol-formaldehyde condensation reaction as a nitrogen source. Since N-phenylmaleimide has been co-condensed in the phenol-formaldehyde resin, the N element can be uniformly and effectively doped into the graphite layer during the subsequent coating and carbonization. While effectively improving the conductivity of the material, the transmission rate is fully improved, and the binding site is also fully improved, thereby greatly improving the rate performance of the modified artificial graphite obtained; at the same time, the N-phenylmaleimide-modified phenol-formaldehyde resin can form a richer pore structure than pure phenol-formaldehyde resin after carbonization, thereby providing more lithium storage space, so that the modified artificial graphite obtained has high capacity and stable cycle performance.
[0010] Preferably, in step S1, the phenolic compound is at least one of phenol, aminophenol, nitrophenol, catechol or resorcinol, the aldehyde compound is at least one of formaldehyde, acetaldehyde, propionaldehyde, valeraldehyde or benzaldehyde; and the catalyst is at least one of oxalic acid, hydrochloric acid, sulfuric acid or p-toluenesulfonic acid.
[0011] Preferably, the mass ratio of the N-phenylmaleimide, the phenolic compound, the aldehyde compound and the catalyst is 2-4:10:2-4:0.5-1.
[0012] Preferably, the polycondensation reaction is carried out at a temperature of 60-90°C and a time of 6-12 hours.
[0013] Preferably, in step S2, the artificial graphite is obtained by crushing, grinding, shaping and graphitizing the artificial graphite raw material;
[0014] Preferably, the artificial graphite raw material is at least one of petroleum coke, needle coke, pitch coke or calcined coke;
[0015] Preferably, the particle size D50 of the artificial graphite is 10-13 μm.
[0016] Preferably, in step S2, the mass ratio of the nitrogen-containing phenolic resin to the artificial graphite is 100:10-30;
[0017] Preferably, the organic solvent is at least one of tetrahydrofuran, water, ethanol, pyridine or N,N-dimethylformamide.
[0018] Preferably, in step S2, before the liquid phase coating, the artificial graphite is also subjected to grafting modification with an alkenyl silane coupling agent;
[0019] Preferably, the alkenyl silane coupling agent is at least one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl methyl dimethoxy silane or vinyl methyl diethoxy silane;
[0020] Preferably, the liquid phase coating further comprises polymerizing the nitrogen-containing phenolic resin and the artificial graphite under the condition of an azo initiator.
[0021] In the present invention, after artificial graphite is grafted and modified by an alkenyl silane coupling agent, alkenyl groups are grafted on the surface of the artificial graphite. When the artificial graphite is coated with the nitrogen-containing phenolic resin in liquid phase, since the nitrogen-containing phenolic resin contains the structure of N-phenylmaleimide and its molecular chain also contains alkenyl groups, the nitrogen-containing phenolic resin can be polymerized on the surface of the artificial graphite under the condition of an azo initiator, thereby further ensuring the effective adsorption and wrapping of the nitrogen-containing phenolic resin on the surface of the artificial graphite, and finally forming a tightly bound carbon shell layer with rich pore structure on the surface of the artificial graphite, thereby further improving the compaction density and electronic conductivity of the obtained modified artificial graphite, and obtaining more excellent electrochemical performance.
[0022] Preferably, in step S2, the temperature of the carbonization treatment is 1300-1600°C and the time is 3-5h;
[0023] Preferably, the inert atmosphere is nitrogen, argon or helium.
[0024] The present invention also provides a nitrogen-containing resin liquid-phase coated modified artificial graphite, which is prepared by the above preparation method.
[0025] The present invention also proposes an application of the nitrogen-containing resin liquid-phase coated modified artificial graphite in lithium-ion batteries.
[0026] The present invention provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, which comprises polymerizing N-phenylmaleimide, a phenolic compound and an aldehyde compound under catalyst conditions to prepare a nitrogen-containing phenolic resin, and then performing liquid-phase coating treatment on artificial graphite using the nitrogen-containing phenolic resin, and then performing high-temperature carbonization to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite. The entire preparation method of the present invention is simple and efficient, and the obtained modified artificial graphite has excellent rate performance, capacity and first effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a flow chart of the method for preparing modified artificial graphite described in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0029] Example 1
[0030] Reference Figure 1 This embodiment provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, which specifically includes:
[0031] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12.38 μm);
[0032] (2) 110 mL of formaldehyde solution (concentration of 37%), 40 g of N-phenylmaleimide and 10 g of oxalic acid were added to a reaction flask, heated to 70° C. and stirred until all the raw materials were dissolved, then 140 g of phenol was added, and the mixture was stirred and reacted for 8 h. Then 100 mL of hot water was added to the resulting reaction solution for dissolution and washing. After standing and separating the liquids, the resulting product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a nitrogen-containing phenolic resin;
[0033] (3) 100 g of the above-mentioned artificial graphite and 20 g of the above-mentioned nitrogen-containing phenolic resin are added to an appropriate amount of tetrahydrofuran and stirred and mixed. The coating is completed after 1 hour. The precursor is then filtered and dried to obtain a precursor. The precursor is calcined at 1500° C. for 4 hours under an Ar atmosphere to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite.
[0034] Example 2
[0035] This embodiment provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, which specifically includes:
[0036] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12.38 μm);
[0037] (2) 75 mL of formaldehyde solution (concentration of 37%), 50 g of N-phenylmaleimide and 10 g of oxalic acid were added to a reaction flask, heated to 60° C. and stirred until all the raw materials were dissolved, and then 140 g of phenol was added. After the reaction was stirred for 12 h, 100 mL of hot water was added to the resulting reaction solution for dissolution and washing. After standing and separating the liquids, the resulting product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a nitrogen-containing phenolic resin;
[0038] (3) 100 g of the above-mentioned artificial graphite and 10 g of the above-mentioned nitrogen-containing phenolic resin are added to an appropriate amount of tetrahydrofuran and stirred and mixed. The coating is completed after 1 hour. The precursor is filtered and dried to obtain a precursor. The precursor is calcined at 1300° C. for 5 hours under an Ar atmosphere to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite.
[0039] Example 3
[0040] This embodiment provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, which specifically includes:
[0041] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12 μm);
[0042] (2) 150 mL of formaldehyde solution (concentration 37%), 30 g of N-phenylmaleimide and 10 g of oxalic acid were added to a reaction flask, heated to 90° C. and stirred until all the raw materials were dissolved, then 140 g of phenol was added, and the mixture was stirred and reacted for 6 h. 100 mL of hot water was added to the reaction solution to dissolve and wash. After standing and separating the liquids, the product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a nitrogen-containing phenolic resin;
[0043] (3) 100 g of the above-mentioned artificial graphite and 30 g of the above-mentioned nitrogen-containing phenolic resin are added to an appropriate amount of tetrahydrofuran and stirred and mixed. The coating is completed after 1 hour. The precursor is filtered and dried to obtain a precursor. The precursor is calcined at 1600° C. for 3 hours under an Ar atmosphere to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite.
[0044] Example 4
[0045] This embodiment provides a method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, which specifically includes:
[0046] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12.38 μm);
[0047] (2) 110 mL of formaldehyde solution (concentration of 37%), 40 g of N-phenylmaleimide and 10 g of oxalic acid were added to a reaction flask, heated to 70° C. and stirred until all the raw materials were dissolved, then 140 g of phenol was added, and the mixture was stirred and reacted for 8 h. Then 100 mL of hot water was added to the resulting reaction solution for dissolution and washing. After standing and separating the liquids, the resulting product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a nitrogen-containing phenolic resin;
[0048] (3) adding vinyl trimethoxysilane to water and stirring and mixing uniformly to obtain an aqueous solution containing 5 wt% vinyl trimethoxysilane, adding acid to adjust the solution pH to 3.5, stirring until the silane coupling agent is fully hydrolyzed, and then adding 200 mL of the obtained solution dropwise to 100 g of the above-mentioned artificial graphite, stirring and mixing for 1 hour, filtering, and drying to obtain artificial graphite grafted with vinyl silane coupling agent;
[0049] (4) The artificial graphite grafted with the alkenyl silane coupling agent and 20 g of the nitrogen-containing phenolic resin are added to an appropriate amount of tetrahydrofuran and stirred and mixed, and then 0.5 g of azobisisobutyronitrile is added, and the mixture is heated to 60° C. and reacted for 4 h to complete the coating. The mixture is filtered and dried to obtain a precursor, and the precursor is calcined at 1500° C. for 4 h under an Ar atmosphere to obtain the artificial graphite modified by the nitrogen-containing resin liquid phase coating.
[0050] Comparative Example 1
[0051] This comparative example proposes a method for preparing modified artificial graphite, which specifically comprises:
[0052] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12.38 μm);
[0053] (2) 110 mL of formaldehyde solution (concentration of 37%) and 10 g of oxalic acid were added to a reaction flask, heated to 70° C. and stirred until all the raw materials were dissolved, and then 140 g of phenol was added. After the reaction was stirred for 8 h, 100 mL of hot water was added to the obtained reaction solution for dissolution and washing. After standing and separating the liquids, the obtained product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a phenolic resin;
[0054] (3) 100 g of the artificial graphite and 20 g of the phenolic resin were added to an appropriate amount of tetrahydrofuran and stirred to mix. The coating was completed after 1 hour. The precursor was filtered and dried to obtain a precursor. The precursor was calcined at 1500° C. for 4 hours under an Ar atmosphere to obtain the modified artificial graphite.
[0055] Comparative Example 2
[0056] This comparative example proposes a method for preparing modified artificial graphite, which specifically comprises:
[0057] (1) After vacuum drying, petroleum-based needle coke (volatile matter: 7%, ash content: 0.1%, S content: not higher than 0.5%) is firstly crushed in a roller mill, then crushed in a mechanical mill, and then subjected to a shaping machine to improve the morphology and remove fine powder, and then graphitized at 3000°C for 48 hours to obtain artificial graphite (D50 particle size: 12.38 μm);
[0058] (2) 110 mL of formaldehyde solution (concentration of 37%) and 10 g of oxalic acid were added to a reaction flask, heated to 70° C. and stirred until all the raw materials were dissolved, and then 140 g of phenol was added. After the reaction was stirred for 8 h, 100 mL of hot water was added to the obtained reaction solution for dissolution and washing. After standing and separating the liquids, the obtained product was purified with an ethanol-water solution and dried overnight under vacuum at 90° C. to obtain a phenolic resin;
[0059] (3) 100 g of the artificial graphite, 16.5 g of the phenolic resin and 3.5 g of N-phenylmaleimide were added to an appropriate amount of tetrahydrofuran and stirred to mix. The coating was completed after 1 hour. The precursor was filtered and dried to obtain a precursor. The precursor was calcined at 1500° C. for 4 hours under an Ar atmosphere to obtain the modified artificial graphite.
[0060] The modified artificial graphite described in the embodiment and the comparative example were respectively tested for particle size. The particle size test was performed using a laser particle size distribution analyzer MS2000. The results are shown in Table 1 below.
[0061] The modified artificial graphite described in the embodiment and the comparative example was respectively mixed with conductive carbon black (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 95:1:1.5:2.5 in water and evenly mixed. After being evenly coated on a copper foil, it was placed in a vacuum drying oven at 120°C and dried for 12 hours, and pressed into a negative electrode sheet. A 1 mol / L LiPF6 solution (solvent is EC / DMC / DEC, v / v=1:1:1) was used as an electrolyte, a metal lithium sheet was used as a counter electrode, and a Cellgard2400 microporous polypropylene membrane was used as a diaphragm. The cells were assembled into button cells in a deoxygenated and dehydrated glove box filled with argon.
[0062] The button cell was placed on a LAND battery tester for electrochemical performance testing, with a charge and discharge voltage range of 0.005-2.0V and a charge and discharge current of 0.1C, to obtain the first discharge capacity and first coulomb efficiency of the nitrogen-containing resin liquid phase coated modified artificial graphite, and the results are shown in Table 1 below;
[0063] The battery was charged and discharged at a rate of 1C / 1C or 3C / 1C, and a full charge and discharge cycle test was performed until the capacity of the lithium-ion battery decayed to 80% of the initial capacity. The number of cycles was recorded. The results are shown in Table 1 below.
[0064] Table 1 Performance test results of the modified artificial graphite described in the examples and comparative examples
[0065]
[0066] It can be seen from Table 1 above that, compared with the comparative example, the modified artificial graphite described in the embodiment has high discharge capacity, first efficiency and cycle rate performance, and is suitable for lithium-ion batteries with high energy density and fast charging requirements.
[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing nitrogen-containing resin liquid-phase coated modified artificial graphite, characterized in that: The steps include: S1, subjecting N-phenylmaleimide, a phenolic compound, an aldehyde compound and a catalyst to a polycondensation reaction to obtain a nitrogen-containing phenolic resin; S2, adding the nitrogen-containing phenolic resin and artificial graphite into a solvent for liquid-phase coating, and then performing carbonization treatment to obtain the nitrogen-containing resin liquid-phase coated modified artificial graphite.
2. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to claim 1, characterized in that: In step S1, the phenolic compound is at least one of phenol, aminophenol, nitrophenol, catechol or resorcinol, the aldehyde compound is at least one of formaldehyde, acetaldehyde, propionaldehyde, valeraldehyde or benzaldehyde; and the catalyst is at least one of oxalic acid, hydrochloric acid, sulfuric acid or p-toluenesulfonic acid.
3. The method for preparing modified artificial graphite coated with nitrogen-containing resin liquid phase according to claim 2, characterized in that: The mass ratio of the N-phenylmaleimide, the phenolic compound, the aldehyde compound and the catalyst is 2-4:10:2-4:0.5-1.
4. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to any one of claims 1 to 3, characterized in that: The temperature of the polycondensation reaction is 60-90° C. and the time is 6-12 hours.
5. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to any one of claims 1 to 4, characterized in that: In step S2, the artificial graphite is obtained by crushing, grinding, shaping and graphitizing the artificial graphite raw material; Preferably, the artificial graphite raw material is at least one of petroleum coke, needle coke, pitch coke or calcined coke; Preferably, the particle size D50 of the artificial graphite is 10-13 μm.
6. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to any one of claims 1 to 5, characterized in that: In step S2, the mass ratio of the nitrogen-containing phenolic resin to the artificial graphite is 100:10-30; Preferably, the organic solvent is at least one of tetrahydrofuran, water, ethanol, pyridine or N,N-dimethylformamide.
7. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to any one of claims 1 to 6, characterized in that: In step S2, before the liquid phase coating, the artificial graphite is also subjected to grafting modification by an alkenyl silane coupling agent; Preferably, the alkenyl silane coupling agent is at least one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl methyl dimethoxy silane or vinyl methyl diethoxy silane; Preferably, the liquid phase coating further comprises polymerizing the nitrogen-containing phenolic resin and the artificial graphite under the condition of an azo initiator.
8. The method for preparing the nitrogen-containing resin liquid-phase coated modified artificial graphite according to any one of claims 1 to 7, characterized in that: In step S2, the carbonization treatment is carried out at a temperature of 1300-1600°C and for a time of 3-5 hours; Preferably, the inert atmosphere is nitrogen, argon or helium.
9. A nitrogen-containing resin liquid phase coated modified artificial graphite, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nitrogen-containing resin liquid phase coated modified artificial graphite according to claim 9 in lithium ion batteries.